Critica a Critica - Freitas, Padre Senna (Manoel Malheiro, Editor, 1879)
Stamp
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage

No Presbyterio e No Templo - Freitas, Padre Senna (Fornecedores da Casa de Bragnca, 1884)
Keywords: 1.Conservation 保護; 2.Damage